住宅用構造建材「JFEフレームキット」の性能 (薄板建材特集号) - 江森, 邦夫; 坂本, 義仁; 高木, 伸之 (Journal of Financial Economics, 2009)
For the 1st time, we directly measured the potential distribution inside org. semiconductors. Combined spectroscopic measurements are performed on MDMO-PPV layers on Au and Yb substrates, using a scanning tunneling microscope (STM). The results are analyzed with a model that treats both current injection and bulk transport in detail. Tip height-bias curves, which are taken by following the height of the STM tip as a function of bias, while the STM feedback system is active, reflect the potential distribution between tip and sample electrode